Copper Complexes of Dithiocarbamates and Thiuram Disulphides of Diethylenetriamine Based Schiff Bases - Vijayanthimala, R.; Swathy, C.H. (Asian Journal of Chemistry, 2011)
Tetranuclear Cu(II) complexes of dithiocarbamates and Cu(I) complexes of thiuram disulphides which are derived from diethylenetriamine based Schiff bases are reported. Dithiocarbamate complexes were formed from Schiff bases of diethylenetriamine and salicylaldehyde/acetophenone while thiuram disulphide complexes were done with Schiff bases formed from diethylenetriamine and salicylaldehyde/cinnamaldehyde/ acetophenone/benzophenone. The complexes have been characterized by elemental and thermal analysis, magnetic studies, IR, UV-VIS, NMR, CVM and X-ray photoelectron spectroscopic studies. Antibacterial studies on some of the Cu(I) complexes of thiuram disulphide are promising against Klebsiella pneumonia, Salmonella typhi, Escherichia coli, Enterococcus faecalis, Pseudomonas aeruginosa, Proteus vulgaris, Staphylococcus epidermis, methicilline resistant Staphylococcus aureus, ciprofloxin resistant E. coli and carbapennen resistant Acetobacter baumanii.